Adversative Cojuncts in The Academic Article of Indonesian Scholars - Agustinus Ngadiman; Connie Tanone (Widya Mandala Surabaya Catholic University, 2014)
This study focuses on the English adversative conjunctions empl0yed by Indonesian scholars in their academic essays. The data sources for this study were twenty introduction part of the academic writing written by Indonesian EFL teachers published I TEFLIN journals in 2002 – 2011. The instrument of this study was the writer herself. The data were analyzed based on the categorization of adversative conjunction by Murcia and Freeman (1999). The study reveals that there were variety of adversative conjuncts used in the academic essays,: (1) proper, (2) contrastive, (3) correction, (4) dismissal but not all the adversative conjuncts were appropriately used which might not be realized by many writers. 85% of the writers misused the adversative conjuncts in their papers. The might be two possible causes of errors: (1) false-concept of hypothesis and (2) the interference of the L1.